Pseudopolycope (P.) andeep sp. nov. from the deep Southern Ocean (Crustacea, Ostracoda, Cladocopina) - Karanovic, Ivana; Brandão, Simone Nunes (Zootaxa, 2013)
Polycopids are one of the most diverse and often very abundant ostracod group in the deep sea. The true diversity of polycopids today inhabiting this environment, however, is very poorly known, because most of the studies identify ostracod material to the genus level, and they are based on the shell characters only. In this paper we describe Pseudopolycope (Pseudopolycope) andeep sp. nov. collected during the ANDEEP-SYSTCO I expedition in 2007 in the Atlantic Sector of the Southern Ocean. The new species was collected from 2,063 m depth. It differs from other 18 Recent Pseudopolycope Chavtur, 1981 species by (1) a peculiar morphology of the structures between claws on the uropodal lamellae; (2) morphology of the mandibular exopod; and (3) ornamentation of the shell. This is the first description of a living polycopid species from the deep Southern Ocean.